Pengaruh Komisaris Independen, Komite Audit, Kepemilikan Institusional Dan Kualitas Audit Terhadap Integritas Laporan Keuangan Di Perusahaan Sub Sektor Transportasi Yang Terdaftar Di BEI Tahun 2017-2019 - Alberto Yakob Kristian Marpaung; Laura Raze Tinambunan; Irma Natallia Bangun; Enda Noviyanti SimorangkirAlbertomarpaung8@gmail.com1 (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
One of the most important things in the financial statements of a company is the integrity of financial reports. Integrity of financial reports, especially in the transportation company sector, there are some that are not in accordance with the standard provisions of the IDX and there are also some transportation companies that do not publish annual financial reports on the IDX. This research was conducted. to analyze the effect of independent commissioners, audit committee, institutional ownership and audit quality on the integrity of financial statements. Integrity of financial statements is the dependent variable in this study, while independent commissioners, audit committee, institutional ownership and audit quality are independent variables in this study. This research is 25 transportation companies listed on the IDX in 2017-2019. In this study the sample was selected using the purposive sampling method. Data analysis was made using classical assumption tests and hypothesis testing using the linear method. double ier. The results of this research show that the independent commissioners, audit committee, institutional ownership and audit quality have no effect on the integrity of the financial statements. Keywords: Independent Commissioner, Audit Committee, Institutional Ownership, Audit Quality, Financial Report Integrity